Ética, mudança estrutural e desenvolvimento : três ensaios sobre economia brasileira - Batista, Álvaro Maia (2021)
The aim of this thesis is to investigate how ethics, structural change and economic development are articulated in the recent Brazilian economic trajectory (since the 1980s). As methodological strategy, a bibliographical research will be carried out with critical analysis of texts that relate to the theme. A quantitative approach will also be used to calculate the Relative Structural Modernization Index (IMER), which will help to understand how the techno-productive evolution of these regional (administrative policy) subdivisions took place. The predominant method of analysis will be inductive-deductive history, as all information and data will be analyzed with a view to understanding that historically situated articulation, while advancing in the discussion of theories that seek to understand the causes of underdevelopment in Brazil . The historical absence of a nationalist elite in the country tends to hamper Brazil's developmental trajectory, while at the same time pointing to the deepening of democracy (through politics) as a way to overcome deleterious social structures.